Primary Hypoadrenocorticism in a Thai Mixed Dog: Case Report - Nuamai, Pongsiri; Rungpupradit, Jetsada (Journal of Mahanakorn Veterinary Medicine, 2022)
A 5-year-old female mixed Thai dog was referred to The Small Animal Teaching Hospital, Faculty of Veterinary Medicine, Mahanakorn University of Technology with presenting signs of 8-10% dehydration, bradycardia (44 bpm) and systemic hypotension (systolic blood pressure 50 mmHg). Laboratory results showed azotemia and isosthenuric urine (1.015). Blood electrolytes found hyperkalemia (6.81 mmol/l), hyponatremia (124 mmol/l) and low Na:K ratio (18:1). An adrenocorticotropic hormone (ACTH) stimulation test was performed, and the low level of cortisol was observed in both pre and post period of tests. From Laboratory results and ACTH stimulation test, primary hypoadrenocorticism was diagnosed. The Addison crisis was corrected by using isotonic crystalloid (0.9% NaCl) in combination with colloid (Tetraspan®) for treatment of hypovolemic shock. Calcium gluconate and sodium bicarbonate were used to correct hyperkalemia and bradycardia. After stabilizing the dog, hormone supplements were started by using dexamethasone. The combination of prednisolone with fludrocortisone were dispensed for continuing hormone supplements at home. After the 2-month period of treatment, fludrocortisone was substituted to desoxycorticosterone pivalate (DOCP) due to the dog’s inability to maintain the balance of Na:K ratio. With this treatment the dog responded well and was able to maintain the balance of Na:K ratio.